Employment effects of regional climate policy: The case of renewable energy promotion by feed-in tariffs - Peter Heindl; Sebastian Voigt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
For the case of the German state of Baden-Wuerttemberg, production and employment effects of the promotion of renewable energy sources are examined based on a regionalized input-output table. Our findings suggest that policy actions promoting renewable energy types do not necessarily create new jobs and additional turnover for the whole economy. They rather induce a structural change of the economy since other investments might be crowded out by investments in installations of renewable energy and the demand in other sectors might decrease. However, if the producers of the installations are able to export parts of their products to the rest of Germany and/or the rest of the world, these crowding out effects can be attenuated and turnover and employment effects might be positive for the state in total.
urn:nbn:de:bsz:180-madoc-326164
Keywords: C67; Q42; R11; 330; Renewable energy; Employment effects; Input output